High Salinity Intensive Seaweed Growth Rate in Aquaponic Systems - Panasani, Manella Nurul Uma; Alamsjah, Moch Amin; Lamid, Mirni; Shaumi, Ami; Rozaimi, Mohammad (Department of Aquaculture, 2024)
Aquaponics is a closed recirculating aquaculture method combined with hydroponics. This method is very alternative for raising fish while growing plants in specially designed media. The mechanism obtained is very effective and efficient, plants can utilize fish waste as nutrients for plant growth. Poisonous fish waste in ponds can be reduced by plants as nutrients for organic substances. This can enhance profitable bio-integrated food production systems. Plants will serve as vegetation filters. This study aimed to determine the effectiveness of aquaponic treatment in high-salinity water by observing the growth in three species of seaweed namely Gracilaria sp., Sargassum sp., and Kappaphycus alvarezii. The research design used the LSD method and was carried out for 63 days. Data analysis using Analysis of Variance (ANOVA) then continued with the test Duncan's Multiple Range Test. The research method involved making aquaponic media including preparing containers for seaweed cultivation and fish and shrimp farming, observing seaweed growth rates, and measuring water quality. Aquaponic treatment can increase the growth rate of intensively cultivated seaweed. The results showed the best weight growth rate in the aquaponic treatment of Gracilaria sp. with a value of 12.33 grams than Kappaphycus alvarezii 11.33 grams and Sargassum sp. 10.83 grams.